Impact of maternal antenatal nutrition and infection treatment interventions on Longitudinal Infant Development and Growth in rural Ethiopia: protocol of the LIDG child follow-up study - Alemayehu Worku; Yemane Berhane; Luke C Mullany; Charles A Nelson; Lian V Folger; Anne CC Lee; Maria Andersson; Parul Christian; Krysten North; Yoseph Yemane Berhane; Nebiyou Fasil; Sitota Tsegaye; et al. (BMJ Paediatrics Open)
Introduction Maternal undernutrition and inflammation in utero may significantly impact the neurodevelopmental potential of offspring. However, few studies have investigated the effects of pregnancy interventions on long-term child growth and development. This study will examine the effects of prenatal nutrition and infection management interventions on long-term growth and neurodevelopmental outcomes of offspring.Methods The Enhancing Nutrition and Antenatal Infection Treatment (‘ENAT’) study (ISRCTN15116516) was a pragmatic, open-label, 2×2 factorial, randomised clinical effectiveness study implemented in 12 rural health centres in Amhara, Ethiopia. The study enrolled 2399 pregnant women who were randomised to receive routine care, an enhanced nutrition package (iron and folic acid, monthly household supply of iodised salt, and micronutrient-fortified balanced energy protein supplement for undernourished women), an enhanced infection management package (genitourinary tract infection screening and treatment, and enhanced deworming), or both packages. In the present Longitudinal Infant Development and Growth study, a subset of 480 children of mothers from ENAT will be recruited equally from each of the four study arms and visited at 12, 18, and 24 months of postnatal age. We will evaluate a range of domains and deploy multiple measures to assess child neurodevelopment, including resting electroencephalography and visual evoked potentials, Hammersmith Infant Neurological Examination, eye-tracking, Bayley Scales of Infant and Toddler Development (Bayley-III), and Magnetic Resonance Imaging (MRI).Discussion This study will advance understanding of the impact of nutrition and inflammation in pregnancy on long-term offspring neurodevelopment. This study aims to fill a critical knowledge gap on the benefits of prenatal interventions to promote the health of mothers and their offspring.Ethics and dissemination This study was approved by the Institutional Review Boards of Addis Continental Institute of Public Health (ACIPH/IRB/002/2022) and Mass General Brigham (2023P000461). Results will be disseminated to local and international stakeholders.Trial registration number NCT06296238.